Methodology for Assessing the Degree of Internationalization of Business Academic Study Programmes - Dan-Cristian Dabija; Catalin Postelnicu; Nicolae Al. Pop (Amfiteatru Economic Journal, 2014)
The purpose of this paper is to develop a methodology for assessing the degree of internationalization of undergraduate, Master's and doctoral business programmes with the aid of complex indicators designed to capture the vast array of characteristics displayed by these programmes and contribute to their promotion in the international academic competition. The methodology should include both general indicators applicable to any study programme and some indicators that are specifically developed for business study programmes. No consensus exists in the internationalization literature and practice over the actual scope and the indicators to be considered in the implementation of such a study. Researchers rather propose methods for assessing and prioritizing universities and/or faculties and lay down a lot of criteria according to which rankings are developed. These rankings are mainly focused on the level of internationalization of socioeconomic and engineering study programmes.
Keywords: I21; I23; P36; P46; 330; internationalization of higher education study programmes; business education; academic study programmes; indicators for measuring business education; scoring model